2022
DOI: 10.3389/fenvs.2022.1018372
|View full text |Cite
|
Sign up to set email alerts
|

The temporal and spatial pattern evolution of land-use carbon emissions in China coastal regions and its response to green economic development

Abstract: Carbon emissions based on land use change have attracted extensive attention from scholars, but the current land use carbon emission accounting model is still relatively rough. Despite the continuous promotion of China’s ecological civilization strategy, whether green economic development promotes carbon emission reduction remains to be studied. This study uses the Exploratory Spatial-temporal Data Analysis (ESTDA) framework system to revise the land-use carbon emission accounting model; it integrates the NDVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In the process of urban land use, undesired outputs such as sewage and exhaust gases were also generated. Therefore, some scholars have included pollutants as undesired outputs in the ULUE evaluation system (Pan et al, 2022;. For example, Wang et al (2022) included carbon emissions as an undesired output in their comparative study of construction land use efficiency in China and United States; similarly measured ULUE in three major urban agglomerations in China using carbon emissions as an undesired output and found that technological progress was the main driver of land use efficiency improvement in each urban agglomeration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the process of urban land use, undesired outputs such as sewage and exhaust gases were also generated. Therefore, some scholars have included pollutants as undesired outputs in the ULUE evaluation system (Pan et al, 2022;. For example, Wang et al (2022) included carbon emissions as an undesired output in their comparative study of construction land use efficiency in China and United States; similarly measured ULUE in three major urban agglomerations in China using carbon emissions as an undesired output and found that technological progress was the main driver of land use efficiency improvement in each urban agglomeration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jiao and Sun 2021) constructed a comprehensive evaluation index system of China's inter-provincial digital economy based on four dimensions: digital foundation, digital application, digital innovation, and digital transformation, and then launched a spatial and temporal heterogeneity of China's inter-provincial digital economy development level and their influencing factors in a spatial SAR analysis (Jiao and Sun, 2021). Pan et al (2021) established an evaluation index system for digital economy development from the four aspects of digital economy infrastructure, digital industrialization, industrial digitalization and digital governance, and used the entropy method for evaluation, finding that the development of digital economy showed an obvious ladder distribution among provinces (Pan et al, 2021). Secondly, the comprehensive evaluation of ecological environment quality.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be seen, the carbon peaking and carbon neutralization of China's coastal provinces can not only promote the sustainable development of coastal areas, but also play a significant role in the green and low-carbon transformation of the national economy and the enhancement of international competitiveness [18]. In order to guide the sustainable development of urban residential buildings and provide differentiated governance measures, we consider coastal provinces as the research object and propose the following three issues: To solve these problems, this study proposes a historical carbon emission reduction assessment, carbon emission scenario analysis and low-carbon path research for urban resi-dential buildings in coastal provinces for the first time.…”
Section: Introductionmentioning
confidence: 99%